ComPacked: Terminal year end report - Baylon, Dianne Angellie Sarmiento (Animo Repository, 2022)
ComPacked is a company that innovated a versatile laptop sleeve which is used as a finished product. The main purpose of the product is to be a tool for the protection and organization of the customer's laptop and other valuable items. It is is a partnership business formed by four (4) industrial-capitalist partners, namely Ms. Gianna Michaela D. Lim, Mr. Joshua Luis L. Mabanag, Ms. Dianne Angellie S. Baylon, and Ms. Clarisse I. Gutierrez. The management team is currently studying BS Entrepreneurship at De La Salle University-Manila. Consequently, the management team of ComPacked was able to distinguish the profitability and opportunities that could be deduced by the selling of the laptop sleeves online due to the pandemic, through market research and customer discovery. The primary target market of the company's products are college students identified through market segmentation and data analytics. Moreover, the Terminal Year End Report consists of the company's main activities and strategies, as well as the result of its one-year operation; highlighting departments, namely, operations and logistics, finance, marketing, corporate communications and information technology.